Pengembangan Modul Ajar Terintegrasi Pendekatan TaRL Berbasis Pembelajaran Berdiferensiasi - Yantoro; Muhammad Sholeh; Hendra Budiono; Eka Sastrawati (Jurnal Penelitian Pendidikan IPA, 2024)
This research focuses on the issue of students failing to achieve learning goals due to not learning at their ability level. Educators must have pedagogical competence, including the ability to develop good and creative learning tools to create an active and interesting learning atmosphere. The TaRL approach, developed in elementary schools using differentiated learning, The TaRL approach is designed in line with student achievement, abilities, and needs. Developing a differentiation-based TaRL approach will create an active learning atmosphere and provide learning opportunities according to student needs. Educators must realize that each student is unique and has different qualities from birth. Of course, we need to fulfill their educational needs as best as possible to adapt education to student's needs and skill levels, ensuring they meet the required learning outcomes. The research uses mixed methods, including research and development, validity, and practicality. Data was collected through practice angle and validity instruments, with quantitative and qualitative data used to assess the effectiveness of TaRL modules. The high validity category of product validation showed a high validation rate of 92%, with 96% media validity, 97.16% material validation, and 89.43% language validation. The study also included teachers' and students' opinions on the differentiation-based efficacy of TaRL modules.